Badania eksperymentalne wpływu wysokiej temperatury na stan zachowania surowców krzemiennych - Bobak, Dariusz; Kufel, Bernadeta; Lisowska, Ewa; Mikołajczyk, Anna (My University, 2008)
Flint artifacts are the most com mon finds on the archaeological sites from Early and Middle Stone Age. Considerable part of assemblages often bear traces resulted from high temperature in- fluence. These traces are usually cursorily described, because in the literature there are no complex studies cOl1Cerning heated flint materia!. 111e aim of our experimental studies, carried out in the llatural as well as in the controlled conditions, was to distinguish the features ofheated flint, that are characteristic for four kinds of Polish flint: cretaceous, Jurassie, chocolate and Świeciechów flint and to find the relationships between an appearance of those fcatures, a height of a temperature and time of heating. We believe that the results of our research can be used in the spatial analysis of arehaeological sites.
Experimental research on th einfluence of a high temperature on preservation of flint raw material
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; flint raw material heating; archaeological experiment